From Classroom to Stage: Transformation of Students' Musical Technique Through Big Band Training - A.Z.DE Markus Tarigan; Dwi Kusumawardani; Rien Safrina (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study examines the transformation of musical techniques that occurs in students who take part in big band training, from classroom learning to performance on stage. Big band as a jazz ensemble popular from the Swing Era of 1935 to the late 1940s offers a unique opportunity for students' musical development. This study observed changes in students' technical skills, understanding of dynamics, improvisation and confidence through a qualitative approach by observing 30 high school students during a six-month training program. Results showed significant improvements in the ability to read scores, instrument playing techniques, and aesthetic understanding of big band music. The main challenge identified was the adaptation of marching band playing habits to the big band context, especially in terms of playing dynamics. A training model combining regular practice, music appreciation, and professional guidance proved effective in transforming students' musicality skills from beginner level to being able to perform on stage with appropriate big band aesthetic standards.